Talking in a language that everyone can understand? Clarity of speeches by the ECB Executive Board - Bjerkander, Lena; Glas, Alexander (Journal of International Money and Finance, 2024)
We use data on speeches held by members of the European Central Bank's (ECB) Executive Board to analyze whether the clarity of central bank communication has increased over time. Employing readability measures as proxy variables, we find that the clarity of information provision is trending upward since the inception of the ECB. The increase is gradual, rather than being induced by changes in the board composition or major macroeconomic events. We also show that clarity is higher for speeches aimed at general audiences and for speeches by female speakers. Moreover, we find that higher clarity is associated with more optimistic media sentiment about the ECB and a stronger relationship between speech and media sentimen
Keywords: Central bank communication Monetary policy transparency Clarity Readability